Studi Perbandingan Hukum Perwujudan Pertanggungjawaban Pidana Korporasi antara Inggris dan Indonesia - Rayhan Wardhana Hascarya Dwiyantama (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2023)
A corporation is a legal entity established with a certain amount of capital to carry out business activities in an area. The implementation of corporate activities must comply with all applicable regulations in the region. However, there is the possibility of rules violation, for example, committing a crime so that they must be held responsible. Corporate criminal liability implements in countries such as the UK and Indonesia. The two countries have characteristics related to this aspect, which raises questions regarding the manifestation of corporate criminal responsibility in the UK and Indonesia, including their differences and similarities. This study aims to describe corporate criminal responsibility in England as a pioneer country and Indonesia as a civil law country that had never recognized this practice. The research explanation expects to make the reader aware of the embodiments, differences, and similarities. This study applies a normative juridical method that uses literary sources to answer problems and a comparative law approach to explain the differences and similarities of corporate criminal responsibility. The study results prove that corporate criminal liability in England and Indonesia has characteristics with differences and similarities.